Growth and Yield of TSS-Derived Shallot (Allium cepa L. var. aggregatum) under Varying NPK Mutiara Fertilizer Doses in Lowland Central Java - Kharis Triyono; Sartono Joko Santosa; Elly Istiana Maulida (Acitya Wisesa: Journal of Multidisciplinary Research, 2026)
True Shallot Seed (TSS) presents a viable alternative to conventional bulb-based propagation in shallot cultivation, offering benefits such as lower seed costs, reduced pathogen transmission, and more uniform crop establishment. Nevertheless, TSS-derived plants display distinct physiological and developmental traits that necessitate specific adjustments in nutrient management, particularly concerning inorganic fertilizer application rates. This study was undertaken to examine the growth and yield performance of TSS-grown shallots of the Sanren F1 variety in response to varying doses of NPK Mutiara fertilizer (16:16:16). A field experiment was executed in Bangsri Village, Karangpandan District, Karanganyar Regency, Central Java, Indonesia, over the period from May to August 2025. The trial employed a Randomized Complete Block Design featuring a single treatment factor comprising five NPK Mutiara dosage levels: 0, 75, 150, 225, and 300 kg ha⁻¹, with each treatment replicated five times. The variables observed included plant height, leaf number, bulb count per plant, fresh bulb weight, and dry bulb weight per plant. Collected data were subjected to analysis of variance at a 95 percent confidence interval, followed by the Honestly Significant Difference test at the 5 percent level whenever significant treatment effects were identified. The results revealed that NPK Mutiara dose significantly influenced plant height, fresh bulb weight, and dry bulb weight, whereas no significant effects were observed on leaf number or bulb number per plant. The application of 75 kg ha⁻¹ produced increases in fresh and dry bulb weight of approximately 74.9 percent and 77.9 percent, respectively, relative to the unfertilized control, and higher doses did not yield statistically meaningful additional improvements. These outcomes suggest that a dosage of 75 kg ha⁻¹ NPK Mutiara represents an efficient fertilization benchmark for TSS-based shallot farming in the lowland environments of Central Java.